2022
DOI: 10.1021/acs.iecr.1c04689
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electrode Configuration Effects on Mass Transfer and Organic Redox Flow Battery Performance

Abstract: For organic redox flow batteries (ORFBs), it is of significance to clarify the influence mechanism of their electrode configuration on the mass transfer inside electrodes and battery performance. A novel three-dimensional (3D) numerical model for ORFBs is established based on the Nernst–Planck and Butler–Volmer theories and is verified by numerous experiments for both the charge and discharge processes. ORFBs equipped with rectangular, trapezoidal, and sector electrodes are investigated, in which the voltage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In some studies, it is found that the energy density of hydrochar, the solid product of HTC, is close to peat and lignite, and it could be used as clean fuel for direct combustion [12]. During HTC, biomass underwent hydrolysis, dehydration, decarboxylation, aromatization and recondensation reactions, in which dehydration and decarboxylation can reduce the H/C and O/C ratios of biomass, thus forming high value-added products, such as solid fuel and electrode materials [13][14][15][16]. In addition, it is proved that the HTC process is mainly affected by reaction temperature [4].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, it is found that the energy density of hydrochar, the solid product of HTC, is close to peat and lignite, and it could be used as clean fuel for direct combustion [12]. During HTC, biomass underwent hydrolysis, dehydration, decarboxylation, aromatization and recondensation reactions, in which dehydration and decarboxylation can reduce the H/C and O/C ratios of biomass, thus forming high value-added products, such as solid fuel and electrode materials [13][14][15][16]. In addition, it is proved that the HTC process is mainly affected by reaction temperature [4].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating renewable energy (e.g., solar, wind) into the grid requires the development of safe and scalable energy storage technologies. Organic-based aqueous flow batteries (AFBs) are acknowledged to be one of the best options due to their advantages of being an earth-abundant elemental resource, a nonflammable solvent, and their decoupling of energy and power. Up to now, a variety of electroactive organics including quinones, phenazines, and viologens have been extensively investigated. Among them, viologen stands out as the unique one that can work well under neutral pH conditions. As a result, the viologen-based electrolyte is mild and noncorrosive, enabling facile battery maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…[18] As opposed to vanadium-based RFB systems, AORFBs employ electrolytes based on organic redox-active species from earth-abundant elements. [19] Among the most well-investigated compounds for AORFBs are quinones, which includes systems using anthraquinones, [20][21][22][23][24] benzoquinones, [5,25,26] and naphtoquinones, [27,28] viologens, [29][30][31][32] TEMPO-based (2,2,6,6tetramethylpiperidine-1-oxyl) organic radicals, [33][34][35][36] and ferrocenes, [6,37] as well as others. [38][39][40][41] The high interest in quinones as active materials in RFB electrolytes is based on both their ability to feature reversible two-electron redox reactions [42] and their structural diversity.…”
Section: Introductionmentioning
confidence: 99%